2023
DOI: 10.3390/diagnostics13020263
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical HER2 Recognition and Analysis of Breast Cancer Based on Deep Learning

Abstract: Breast cancer is one of the common malignant tumors in women. It seriously endangers women’s life and health. The human epidermal growth factor receptor 2 (HER2) protein is responsible for the division and growth of healthy breast cells. The overexpression of the HER2 protein is generally evaluated by immunohistochemistry (IHC). The IHC evaluation criteria mainly includes three indexes: staining intensity, circumferential membrane staining pattern, and proportion of positive cells. Manually scoring HER2 IHC im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…These results may be attributed to the network's lack of access to supplementary texture or tumour microenvironment data, instead relying on the same information presented at a varying scale. Finally, when we apply the ResNet34 network used in Che et al [20] to our dataset, the results are comparable to those previously reported, with an average accuracy of 94%. Thus, the proposed method outperforms other existing methods, as proven by the obtained results with an average accuracy of 97%.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…These results may be attributed to the network's lack of access to supplementary texture or tumour microenvironment data, instead relying on the same information presented at a varying scale. Finally, when we apply the ResNet34 network used in Che et al [20] to our dataset, the results are comparable to those previously reported, with an average accuracy of 94%. Thus, the proposed method outperforms other existing methods, as proven by the obtained results with an average accuracy of 97%.…”
Section: Resultssupporting
confidence: 88%
“…In this specific case, a 9.76% of the tissue is reported as 3+, so the system evaluates the slide as a 3+ positive, providing a warning to check for equivocal tissue regions for further analysis by the pathologist. Comparing the outcomes achieved using the proposed method to those cited in the current literature [13][14][15][16][17][18][19][20], a comparison can be drawn with the outcomes of five of the mentioned methods, all of which used the AIDPATH database [14][15][16][17]19]. Among these, Cordeiro et al [14] reported the highest accuracy rate of 94%.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations